Strategic human resource management, organisational culture and firm performance in the insurance industry in Malaysia / Loo Leap Han - Loo, Leap Han (2014)
The subject of strategic human resource management (SHRM) has attracted a great deal of attention among the academicians and human resource practitioners of its importance for firm performance. This attention reflects the growing development of human resource competencies and practices necessary for gaining competitive advantage. However, less is known about how SHRM process is implemented and what impact it has on firm performance to attain sustainable competitive advantage. Furthermore, by drawing on the literature on SHRM and firm performance, this study elaborates that firms can employ a specific combination of SHRM practices that are internally consistent and complement of each other to facilitate the achievement of superior performance in Malaysian context. This study focused at firm level and demonstrates the potential for SHRM practices to serve as firm-level sources of enhancing performance that are consistent with the resource-based view of the firm and configurational perspective approach. In making this contribution to the SHRM literature, this study also attempts to examine the role of organisational culture in the SHRM implementation process and its effect on firm performance. In addition, the findings illustrate SHRM at macro level in established organisations and can further utilise these practices at small and developing organisations in Malaysia and other Asian countries. The conceptual model of this study provides a valuable theoretical contribution by explaining the eight SHRM practices namely SHRM alignment in the organisation, recruitment and selection, training and development, compensation and benefits, performance appraisal, internal communication, career planning, and job design should v be combined and aligned that will lead to direct effects on different firm performance’s outcomes (rate of productivity, customer service, quality of products, and sales growth). Organisational Assessment Culture Instrument (OCAI) was used to identify the perceived dominant culture type and examined organisational culture as mediator in the relationship between SHRM and performance. The study was conducted through a primary data survey of seven major insurance firms in Klang Valley. Stratified random sampling was employed and empirical results from a sample of 312 insurance employees consisting of top management, manager, executive, and non-executive indicate that combination of SHRM practices generate greater synergy between the practices and effects on firm performance compare to single HRM practice. The empirical results of this study show that the combination between SHRM practices have positive effect on specific firm performance’s outcomes; 1) recruitment and selection and performance appraisal on rate of productivity, 2) career planning and SHRM alignment in the organisation on customer service, 3) training and development and career planning on quality of products, and 4) recruitment and selection, career planning, and performance appraisal on sales growth. Overall, results indicate that the combination of recruitment and selection, internal communication, and performance appraisal utilisation is positively associated with overall firm performance. Market culture was identified as the dominant culture type in the insurance industry. The hypothesised mediating role for market culture was partially supported. Similarly, adhocracy culture was also found to mediate the relationship between SHRM and performance. The results reveal that the existence of more than one culture type will create culture dynamism, hence improves firm performance. In sum, these empirical vi findings show the importance of building up organisational culture and eventually pay off in terms of better firm performance. Taken together, the results of this study offer a number of theoretical and practical implications. At a general level, this study supports the resource-based view of the firm and configurational perspective approach, by demonstrating SHRM practices and organisational culture serve as a firm-level source of enhanced performance. Insurance firms in Malaysia are undergoing tremendous environmental changes and business reforms. Therefore, human resource practitioners need to establish effective SHRM practices, building an appropriate and strong culture in order firm can ultimately achieve superior performance.